Seroprevalencia de Leucosis Enzootica Bovina (LEB) y algunos factores de riesgo en bovinos del trópico alto de Boyacá, Colombia - González-Bautista, Edgar-Daniel; Bulla-Castañeda, Diana-María; Lancheros-Buitrago, Deisy-Johana; Giraldo-Forero, Julio-César; Castañeda-Sedano, Leneth-Baggerly; Pulido-Medellín, Martín-Orlando (Revista Científica, 2024)
Enzootic Bovine Leukosis (EBL) is a viral disease that affects cattle and has a worldwide distribution, with national prevalences of 13.5-54.6%. Its symptoms can be imperceptible at first, but they manifest in different ways over time depending on the affected organ. The replication mechanism makes the virus virtually impossible to treat, affecting B lymphocytes and monocytes, which predisposes cattle to the incidence of opportunistic pathogenic agents and turns any type of secretion and excretion into a probable contagion factor. The aim of this study was to determine the seroprevalence of EBL and some risk factors in cattle from the high tropic of Boyacá, Colombia. Serological samples from 385 bovine specimens were taken, which were processed using the commercial SERELISA BLV Ab Mono Blocking kit. Prevalence was determined using the Epi Info statistical software, and determining factors were established, calculating the prevalence ratio to identify risk factors. An apparent prevalence (AP) of 19.72% was found. Females were more seropositive (19.94%) than males (14.29%), and the age group from two to four years showed the highest seropositivity for antibodies against the EBL virus (21.21%), followed by individuals aged more than four (20.63%) and animals under two years old (16.6%). Moreover, the Normande breed was the least seropositive (17.4%), while crossbreeds had a higher seroprevalence (22.22%). Although no variable was identified as a risk factor, it is crucial to pay attention to those that showed a significant statistical association, as they may influence the transmission of the virus.